Hakikat Kebenaran; Perspektif Pengetahuan, Ilmu, Agama dan Filsafat - Dafri Harweli; Ridha Ahida (Journal on Education, 2024)
This research is to find out the nature of truth; perspectives of knowledge, science, religion and philosophy. This research uses a library research method with a qualitative approach. The research results show that: 1) The nature of truth. The emergence of a theory of truth can build knowledge from the views and understanding obtained through existing processes. In order to emphasize theory as a benchmark for truth, we can look at the theory of truth from two very common perspectives, namely: the western-based theory of truth and the theory of truth. The nature of truth is rational, empirical and pragmatic. 2) Knowledge includes reasoning and logic, 3) The characteristics of knowledge are that it is arranged methodically, systematically and coherently about a particular field and reality and can be used to explain certain phenomena in the field (knowledge). 4) Religion is human belief or belief in a teaching that comes from God, the bearer of truth, and 5) philosophy is a science that seriously studies the nature of the truth of all things.